Analysis of Financial Ratios For Financial Distress conditions in Manufacturing Companies - Sita Dewi Riyanti (Pascasarjana Universitas Jenderal Soedirman, 2020)
Bankruptcy does not just happen, but starts from financial difficulties and liquidation, which is commonly referred to as a financial distress. In predicting financial distress, measurements can be made with certain ratios. This study aims to examine the role of financial ratios in predicting financial distress. The sample consists of 24 manufacturing companies on the Indonesia Stock Exchange. The data used are the 2013-2016 financial statements. The 2015-2016 financial reports are used as determinants of financial distress, and the 2013-2014 reports are the data processed in this study. Logistic regression is an analytical tool used to test hypotheses. In this case, the financial ratios of the Altman model and the financial ratios of cash flows will be used to predict the company's financial distress. The results of this study indicate that the ratio of EBITTA, WCTA, RETA, CFOTA has a significant negative effect in predicting financial distress. Meanwhile, the MVETL and SATA financial ratios have no effect in predicting the company's financial distress. The classification power of prediction accuracy in this research model is 83.3%.